2019
DOI: 10.3390/ijms20020434
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle-Mediated Cell–Cell Communication in the Nervous System: Focus on Neurological Diseases

Abstract: Extracellular vesicles (EVs), including exosomes, are membranous particles released by cells into the extracellular space. They are involved in cell differentiation, tissue homeostasis, and organ remodelling in virtually all tissues, including the central nervous system (CNS). They are secreted by a range of cell types and via blood reaching other cells whose functioning they can modify because they transport and deliver active molecules, such as proteins of various types and functions, lipids, DNA, and miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 196 publications
(225 reference statements)
2
94
0
3
Order By: Relevance
“…It is important to note that EVs are considered critical mediators of cell to cell communication through the exchange of different molecules, such as proteins, DNA, RNA species, and metabolites (Caruso Bavisotto et al, 2019). Remarkably, EVs cargo can be modulated by different stimuli to the source cell, exerting pleiotropic effects on the recipient cell (Yoon et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that EVs are considered critical mediators of cell to cell communication through the exchange of different molecules, such as proteins, DNA, RNA species, and metabolites (Caruso Bavisotto et al, 2019). Remarkably, EVs cargo can be modulated by different stimuli to the source cell, exerting pleiotropic effects on the recipient cell (Yoon et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations have been done in the attempt to use chaperones for the corrections of protein misfolding and treatment of human diseases [41]. Among HSPs, HSP60 has been shown to be involved in brain tumors [1,[42][43][44], and preclinical in vitro and in vivo data have shown that curcumin may be an effective treatment for brain tumors [17]. Nevertheless, it remains to be explored what the effect of curcumin on HSP60 s expression and/or function is.…”
Section: Discussionmentioning
confidence: 99%
“…However, the design of this type of drug is hampered by the fact that HSPs are actually more than cytosolic chaperones and should be considered as important regulators of signaling pathways. Their membrane localization and the interactions they maintain with lipids are associated with the facilitation of endocytosis or the release of exosomes and antiapoptotic mechanisms in cancers, for example (81). Thus, the membrane-HSP mechanistic interactions must be decrypted to reduce the toxicity of drugs.…”
Section: Discussionmentioning
confidence: 99%